(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
The current research paper describes the importance of Gomutra (cows urine) in obesity management. For this purpose 30 patients were selected randomly from M.M.M Government Ayurvedic College & Associated Group of hospitals, Udaipur. For diagnostic purpose objective parameters like total body weight of patient, BMI, Measurement of skin-fold thickness, Circumference of Chest, Abdomen, Hip, Mid thigh, biochemical analysis like lipid profile and subjective parameters like Chalatva, Kshudra Swasa Daurbalya, Anga Gaurva, Alasya, Gatrasada, Alpa Vyavaya, Ati Kshudha, Ati Piapasa Nidradhikya, Swedadhikya, Daurgandhya, Snigdhangta, Sandhishool were taken in to consideration. In pathogenesis of Sthaulya, Kapha (Kledaka Kapha), Vata (Samana & Vyana Vayu), Meda (fat /lipid) and Medodhatvagni Mandyata are main responsible factors according to our samhitas1 My hypothesis for this evaluation was based on the facts that Gomutra has all those properties which can be helpful in Samprapti vighatana of obesity i.e.m Tikshna, Ushna, Laghu and Kaphavat shamak etc. I also considered the biochemical analysis on Gomutra and its elemental properties. Keeping this in mind Gomutra was given to every patient according to their age and Kosthagni ranging from 3ml to 5ml with water and all changes were calculated by parameteric and non parameteric tests. In this study cows urine proved very effective in obesity management reduced weight and B.M.I by 6.51% and 6.11% respectively. This research is very important in todays life because the problem of obesity is increasing day by day due to our sedentary life style and it is leading to very fatal diseases.